Do Government Expenditures Shift Private Philanthropic Donations to Particular Fields of Welfare? Evidence from Cross-country Data. (5th January 2018) - De Wit, Arjen; Neumayr, Michaela; Handy, Femida; Wiepking, Pamala
Abstract: Do government expenditures shift private philanthropic donations to particular fields of welfare? We examine this association in the first cross-country study to correlate government expenditures with the level of individual private donations to different fields of welfare using the Individual International Philanthropy Database (IIPD, 2016 ; N country = 19; N individual = 126, 923). The results of the descriptive and multilevel analyses support the idea of crosswise crowding-in; in countries where government expenditures in health and social protection are higher, more donors give to support the environment, international aid, and the arts. The level of giving to different sectors, however, is not associated with government expenditures. The results reject the crowding-out hypothesis and provide a nuanced picture of the relationship between government funding and philanthropic giving across different fields of social welfare.